Electrophotographic member, electrophotographic image forming apparatus, and conductive resin composition
By using a combination of aromatic ring-containing polyester, FSI anions, and double bond-containing cations in the resin layer of the electrophotographic member, the problem of reduced conductivity of the resin layer under long-term use and high voltage environments is solved, and conductivity is achieved Stable effect.
Patent Information
- Application Number
- CN202410959609.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-06-24
- Filing Date
- 2024-07-17
- Publication Date
- 2025-01-21
AI Technical Summary
When using the electrophotographic member for a long time, the resin layer using an ion conductive agent containing an FSI anion is prone to decrease in conductivity, especially in an environment where high voltage is applied.
By using a combination of aromatic ring-containing polyester, fluorosulfonimide anions, and double bond-containing cations in the resin layer, a stable conductive resin composition is formed to suppress changes in conductivity over time.
This resin layer maintains stable conductivity and prevents conductivity degradation over long periods of use and in high-voltage environments, thereby ensuring high-quality performance of electrophotographic components and image forming equipment.
Smart Images

Figure CN119335833A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to an electrophotographic member, an electrophotographic image forming apparatus, and a conductive resin composition. Background Art
[0002] Japanese Patent Application Laid-Open No. 2014-132329 discloses an electroconductive belt for electrophotography obtained by using an ion conductive agent containing a perfluoroalkylsulfonyl imide anion as an anion. Summary of the invention
[0003] In recent years, the regulation of perfluoroalkyl and polyfluoroalkyl substances (hereinafter also referred to as "PFAS") has been considered, which are said to exhibit high environmental persistence and bioaccumulation. Therefore, the inventors of the present invention studied ionic conductive agents that do not have a CF bond in the molecule and contain a bis(fluorosulfonyl)imide anion (hereinafter also referred to as "FSI anion") that does not belong to PFAS. Japanese Patent Application Publication No. 2020-024404 discloses the use of FSI anions in electronic photographic components. Specifically, Example 6 in Japanese Patent Application Publication No. 2020-024404 discloses a developing blade using an FSI anion and a cation containing a long alkyl chain.
[0004] According to studies by the inventors of the present invention, an electrophotographic member having a resin layer imparted with conductivity by using an ion conductive agent containing FSI anions (hereinafter also referred to as "FSI ion conductive agent") is more likely to experience a decrease in conductivity during long-term use than a case where an ion conductive agent containing trifluoromethanesulfonyl imide (TFSI) anions is used.
[0005] At least one aspect of the present disclosure is to provide an electrophotographic member that is less likely to suffer a decrease in conductivity even when used for a long time in an environment where a high voltage is applied. In addition, at least one embodiment of the present disclosure is to provide an electrophotographic image forming apparatus that can stably form high-quality electrophotographic images even when the apparatus is used for a long time. In addition, at least one aspect of the present disclosure is to provide a conductive resin composition that is less likely to suffer a decrease in conductivity even when electricity is applied for a long time.
[0006] At least one aspect of the present disclosure is directed to providing an electrophotographic member, wherein
[0007] The electrophotographic member comprises a resin layer,
[0008] The resin layer has electrical conductivity.
[0009] The resin layer contains
[0010] Polyesters containing aromatic rings and
[0011] a fluorosulfonyl imide anion and a double bond-containing cation, and
[0012] The aromatic ring-containing polyester is a polyester selected from the group consisting of the following polyesters (i) to (iv) or a mixture of two or more polyesters selected from the group consisting of the following polyesters (i) to (iv):
[0013] (i) polyethylene naphthalate;
[0014] (ii) polyethylene terephthalate;
[0015] (iii) a modified polyethylene terephthalate in which the proportion of acid monomer units other than terephthalic acid units in all acid monomer units is 6 mol% or less; and
[0016] (iv) A modified polyethylene naphthalate in which the proportion of acid monomer units other than naphthalenic acid units in all acid monomer units is 6 mol% or less.
[0017] At least one aspect of the present disclosure is directed to providing an electrophotographic image forming apparatus, wherein
[0018] The electrophotographic image forming apparatus includes the above-mentioned electrophotographic member as an intermediate transfer member.
[0019] At least one aspect of the present disclosure is directed to providing a conductive resin composition, wherein
[0020] The conductive resin composition comprises
[0021] Polyesters containing aromatic rings and
[0022] a fluorosulfonyl imide anion and a double bond-containing cation, and
[0023] The aromatic ring-containing polyester is a polyester selected from the group consisting of the following polyesters (i) to (iv) or a mixture of two or more polyesters selected from the group consisting of the following polyesters (i) to (iv):
[0024] (i) polyethylene naphthalate;
[0025] (ii) polyethylene terephthalate;
[0026] (iii) a modified polyethylene terephthalate in which the proportion of acid monomer units other than terephthalic acid units in all acid monomer units is 6 mol% or less; and
[0027] (iv) A modified polyethylene naphthalate in which the proportion of the acid monomer units other than the naphthalene dicarboxylic acid units in all the acid monomer units is 6 mol% or less.
[0028] At least one aspect of the present disclosure can provide an electrophotographic member that is less likely to experience a decrease in conductivity even when used for a long time in an environment where a high voltage is applied. In addition, at least one embodiment of the present disclosure can provide an electrophotographic image forming apparatus that can stably form high-quality electrophotographic images even when the apparatus is used for a long time. In addition, at least one aspect of the present disclosure can provide a conductive resin composition that is less likely to experience a decrease in conductivity even when electricity is applied for a long time.
[0029] Further features of the present invention will become apparent from the following description of exemplary embodiments with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1A and Figure 1B is a diagram illustrating ion dissociation in a resin layer according to one aspect of the present disclosure;
[0031] Figure 2 is a schematic cross-sectional view showing one example of an electrophotographic image forming apparatus; and
[0032] FIG. 3A to FIG. 3D is a diagram illustrating the configuration of an electrophotographic belt according to one aspect of the present disclosure. DETAILED DESCRIPTION
[0033] In the present disclosure, unless otherwise specified, the terms "XX or more and YY or less" and "XX to YY" indicating a numerical range mean a numerical range including the upper limit and the lower limit as the endpoints of the range. In the case of describing the numerical range in sections, the upper limit and the lower limit of each numerical range can be arbitrarily combined. In addition, the unit "Ω / □" of the surface resistivity means "Ω / square". In the present disclosure, a wording such as "at least one selected from the group consisting of XX, YY and ZZ" means any one of XX; YY; ZZ; a combination of XX and YY; a combination of XX and ZZ; a combination of YY and ZZ; or a combination of XX, YY and ZZ.
[0034] As described above, an electrophotographic member having a resin layer to which conductivity is imparted by using an ion conductive agent containing FSI anions (hereinafter also referred to as "FSI ion conductive agent") is more likely to experience a decrease in conductivity during long-term use than a case where an ion conductive agent containing trifluoromethanesulfonyl imide (TFSI) anions is used. It is presumed that the reason why the conductivity of the resin layer tends to decrease when the FSI ion conductive agent is used to impart conductivity is because the molecular size of the FSI anion is small due to the lack of a perfluoroalkyl group.
[0035] Japanese Patent Application Publication No. 2020-024404 points out that the entanglement between the molecular chain of the ion and the matrix resin can inhibit the migration of the ion. In view of the invention disclosed in Japanese Patent Application Publication No. 2020-024404, the inventors of the present invention studied the combination of FSI anion and imidazolium cation bonded to C9-C20 long-chain alkyl, hoping to inhibit the migration of FSI. However, even with such a combination, in the case of an electrophotographic member to which a high voltage is applied, such as an intermediate transfer belt, the beneficial effect of preventing the conductivity from decreasing over time is extremely limited.
[0036] It is speculated that in an electronic photographic member to which a high voltage is applied, even if the FSI anion is combined with an imidazolium cation bonded to a C9-C20 long-chain alkyl group, it is not enough to prevent the migration of the FSI anion with a small molecular size. Therefore, the imidazolium cation migrates to the negative electrode side, the FSI anion migrates to the positive electrode side, and the imidazolium cation and the FSI anion reaching the electrode are respectively reduced and oxidized to lose charge. The conductivity derived from the ionic conductive agent is proportional to the number of carrier ions as a conductive carrier. That is, because the resistivity is the reciprocal of the conductivity, some carrier ions will lose charge if a voltage is applied for a long time. As a result, it is believed that the reduction in the number of carrier ions causes the resistivity to rise.
[0037] Therefore, the inventors of the present invention have conducted research to obtain a conductive resin layer that can prevent conductivity from changing over time even when a voltage is applied, based on the premise of using FSI anions. As a result, the inventors of the present invention have found that a resin layer containing FSI anions, aromatic ring-containing polyesters, and double bond-containing cations is effective for achieving the above purpose.
[0038] The inventors of the present invention believe that the reason why the above-mentioned resin layer can suppress the temporal change in conductivity even when a high voltage is applied is as follows.
[0039] Think Figure 1A As shown, the resin layer imparted with conductivity by the ion conductive agent is generally in a state of equilibrium between the form of a salt of cations 101 and anions 102 and the form of cations 101 and anions 102 dissociating to form carrier ions (103). That is, some ion conductive agents do not dissociate and do not contribute to conductivity.
[0040] Furthermore, in the resin layer according to the present disclosure, if Figure 1B As shown, the π-π interaction (105) between the π electrons in the aromatic ring (104) of the aromatic ring-containing polyester and the π electrons in the double bond-containing cation (101) leads to a state in which the cation-anion (102) bond is weakened and ion dissociation is easy to occur. That is, the equilibrium state shifts to the direction in which the number of carrier ions increases.
[0041] In addition, even if cations and anions migrate in the resin layer and lose charge, which means that the number of carrier ions decreases and the equilibrium state is destroyed, as described above, rapid ion dissociation occurs to maintain the equilibrium state. Therefore, even if the voltage is continuously applied, the number of carrier ions is unlikely to change. Therefore, it is believed that a resin layer that can suppress changes in conductivity even in long-term use can be formed.
[0042] Embodiments of the electrophotographic member of the present disclosure will be described in detail. In addition, the present disclosure is not limited to the embodiments given below.
[0043] <Electrophotographic member>
[0044] The electronic photographic member according to one aspect of the present disclosure has a resin layer having a polyester containing an aromatic ring, a fluorosulfonyl imide anion, and a cation containing a double bond. The resin layer has conductivity. As long as the advantageous effects of the present disclosure are not impaired, the resin layer and the like may contain additives other than these components and the like.
[0045] There is no particular limitation on the form of the electrophotographic member. That is, the electrophotographic member according to one embodiment of the present disclosure may be a belt having an endless form (hereinafter also referred to as an "electrophotographic belt") or an electrophotographic roller having a roller form. The electrophotographic member is preferably an electrophotographic belt, and more preferably an intermediate transfer belt.
[0046] Figure 3A A perspective view showing a conductive belt 300 as an example of an electrophotographic member according to one aspect of the present disclosure.
[0047] An example of a layer structure is a single layer structure in which Figure 3A The cross section of the center line AA' is formed only by the resin layer 301. Figure 3B In this case, the outer surface 301-1 of the resin layer is, for example, a surface for supporting unfixed toner when the conductive belt is used as an intermediate transfer belt, that is, forms the outer surface of the conductive belt.
[0048] Another example is a configuration having a layer structure in which a cross section along line AA' has a base layer 303 and a resin layer 301 covering the outer peripheral surface of the base layer, such as Figure 3CIn this configuration, the outer surface 301 - 1 of the resin layer 301 on the opposite side from the base layer 303 forms the outer surface of the conductive tape.
[0049] Another example is a configuration having a layer structure in which a cross section along line AA' has a resin layer 301 and a surface layer 305 covering the outer peripheral surface of the resin layer, such as Figure 3D In this configuration, the outer surface 305 - 1 of the surface layer 305 on the opposite side from the resin layer 301 forms the outer surface of the conductive tape.
[0050] Another example is a construction (not shown) having a backing layer covering a Figure 3B , Figure 3C or Figure 3D The inner circumference of the conductive belt of the structure shown.
[0051] <Resin Layer>
[0052] The thickness of the resin layer is not particularly limited, but when the electrophotographic member is used as an intermediate transfer belt, the thickness is, for example, preferably 10 to 700 μm, more preferably 50 to 120 μm. By making the thickness of the resin layer fall within the above range, the strength, flexibility, and flex resistance required for the member can be ensured.
[0053] The resin layer may be a layer (surface layer) forming the outer surface of the electrophotographic member. More specifically, in the case where the electrophotographic member is, for example, an intermediate transfer member, the resin layer may be a layer constituting the outer surface of the intermediate transfer belt, which is a supporting surface of the toner image of the intermediate transfer belt. In addition, a treatment agent may be applied to the surface of the resin layer, a surface treatment such as a polishing treatment may be performed, and a surface layer for protecting the surface of the resin layer may be separately provided.
[0054] The materials used in the resin layer will now be described in detail.
[0055] <Aromatic ring-containing polyester>
[0056] The resin layer contains polyester containing an aromatic ring. The polyester containing an aromatic ring is preferably a matrix resin.
[0057] From the viewpoint of having a high aromatic ring ratio in the molecule and being more likely to achieve the advantageous effect of promoting ion dissociation, the aromatic ring-containing polyester is a polyester selected from the group consisting of the following polyesters (i) to (iv) or a mixture of two or more polyesters selected from the group consisting of the following polyesters (i) to (iv):
[0058] (i) polyethylene naphthalate;
[0059] (ii) polyethylene terephthalate;
[0060] (iii) a modified polyethylene terephthalate in which the proportion of the acid monomer units other than the terephthalic acid units in all the acid monomer units is 6 mol% or less (e.g., 0 to 6 mol%); and
[0061] (iv) A modified polyethylene naphthalate in which the ratio of the acid monomer units other than the naphthalene dicarboxylic acid units in all the acid monomer units is 6 mol% or less (eg, 0 to 6 mol%).
[0062] The aromatic ring-containing polyester more preferably includes at least one selected from the group consisting of polyethylene naphthalate, polyethylene terephthalate and modified polyethylene terephthalate. The modified polyethylene terephthalate is preferably isophthalic acid-modified polyethylene terephthalate and naphthalene dicarboxylic acid-modified polyethylene terephthalate, and more preferably isophthalic acid-modified polyethylene terephthalate.
[0063] More preferably, it contains at least one selected from the group consisting of polyethylene naphthalate, polyethylene terephthalate and isophthalic acid-modified polyethylene terephthalate. The aromatic ring-containing polyester is more preferably (i) polyethylene naphthalate, (ii) polyethylene terephthalate or (iii) modified polyethylene terephthalate, wherein the proportion of acid monomer units other than terephthalic acid units in all acid monomer units is 6 mol% or less, and the acid monomer units other than terephthalic acid units are isophthalic acid units.
[0064] In addition, in order to increase the crystallinity and further improve the strength of the resin layer, the aromatic ring-containing polyester more preferably contains at least one polyester selected from the group consisting of polyethylene naphthalate and polyethylene terephthalate. The aromatic ring-containing polyester is still more preferably polyethylene naphthalate or polyethylene terephthalate.
[0065] In the present disclosure, the term "monomer unit" describes the reactive form of a monomeric substance in a polymer. For example, in polyesters, one monomer unit is disposed between ester bonds and, when calculated in mol%, one monomer unit corresponds to one molecule.
[0066] One of the aromatic ring-containing polyesters can be used alone, or a combination of two or more thereof can be used, and the combination can be a blend or an alloy. In addition, other resins can be added as long as the advantageous effects of the present disclosure are not impaired. As other resins, well-known resins can be used. For example, polyether ester amide.
[0067] In addition, a specific example of polyethylene naphthalate is "TN-8065S" (trade name, produced by Teijin Ltd.). In addition, a specific example of polyethylene terephthalate is "TR-8550FF" (trade name; produced by Teijin Ltd.). In addition, a specific example of isophthalic acid-modified polyethylene terephthalate is "IP121B" (trade name; produced by Bell Polyester Products, Inc.; polycondensate of terephthalic acid, isophthalic acid and ethylene glycol).
[0068] From the viewpoint of maintaining the strength of the electrophotographic member, the content of the aromatic ring-containing polyester in the resin layer is preferably 50.0 to 99.0 mass %, more preferably 60.0 to 98.0 mass %, further preferably 70.0 to 98.0 mass %, even more preferably 75.0 to 98.0 mass % relative to the mass of the resin layer.
[0069] <Bis(fluorosulfonylimide) anion>
[0070] The resin layer etc. contains a bis(fluorosulfonyl)imide (FSI) anion as an anion. The bis(fluorosulfonyl)imide anion has a structure represented by the following structural formula (1).
[0071]
[0072] If necessary, the resin layer may contain anions other than the FSI anions as long as the advantageous effects of the present disclosure are not impaired. However, from the viewpoint of further reducing the environmental dependence of the conductivity of the resin layer, the resin layer preferably contains the FSI anions as the only anions.
[0073] Here, as other anions that can be used, anions that do not have a CF bond in the molecule and do not belong to PFAS are preferably used. Examples of anions that do not belong to PFAS include, for example, Cl - Br - ,I - 、AlCl4 - 、N(CN)2 - and anions represented by the following structural formulas (2) to (4).
[0074]
[0075] In the structural formulas (2) to (4), R 21 , R 31 , R 41 and R 42Each independently represents any one selected from the group consisting of a hydrogen atom, a hydrocarbon group having 1 to 18 carbon atoms, and an alkoxy group having 1 to 18 carbon atoms. Examples of the hydrocarbon group include linear and branched saturated hydrocarbon groups, linear and branched unsaturated hydrocarbon groups, substituted and unsubstituted saturated alicyclic hydrocarbon groups, substituted and unsubstituted unsaturated alicyclic hydrocarbon groups, and substituted and unsubstituted aromatic hydrocarbon groups.
[0076] R 21 Preferred examples include a hydrogen atom, a linear or branched alkyl group having 1 to 6 carbon atoms (more preferably 1 to 3 carbon atoms), and a substituted or unsubstituted aryl group, more specifically, an unsubstituted phenyl group or a phenyl group substituted by an alkyl group having 1 to 3 carbon atoms (more preferably 1 or 2 carbon atoms).
[0077] R 31 Preferred examples include alkyl groups having 3 to 15 carbon atoms (more preferably 6 to 12 carbon atoms).
[0078] R 41 and R 42 Preferred examples of each independently include linear and branched alkyl groups having 3 to 15 carbon atoms (more preferably 6 to 12 carbon atoms).
[0079] Examples of the anion represented by the above structural formula (2) include at least one selected from the group consisting of anions listed below.
[0080] The sulfonate ion, methanesulfonate ion, ethanesulfonate ion, 1-butanesulfonate ion, p-toluenesulfonate ion (toluenesulfonate ion), 1-octanesulfonate ion, 1-decanesulfonate ion, 1-tetradecanesulfonate ion, 1-octadecanesulfonate ion, hydrogen sulfate ion, methyl sulfate ion, ethyl sulfate ion, 1-butyl sulfate ion, 1-octyl sulfate ion, 1-decyl sulfate ion, 1-tetradecyl sulfate ion and 1-octadecyl sulfate ion. More preferably, at least one selected from the group consisting of formate ion, acetate ion, p-toluenesulfonate ion and hydrogen sulfate ion.
[0081] Examples of the anion represented by the above structural formula (3) include at least one selected from the group consisting of anions listed below.
[0082] Formate ion, acetate ion, butyrate ion, hexanoate ion, benzoate ion, octanoate ion, decanoate ion, dodecanoate ion, tetradecanoate ion, hexadecanoate ion, octadecanoate ion, methyl carbonate ion, ethyl carbonate ion, butyl carbonate ion, hexyl carbonate ion, octyl carbonate ion, decyl carbonate ion, tetradecyl carbonate ion and octadecyl carbonate ion. Decanoate ion is more preferred.
[0083] Examples of the anion represented by the above structural formula (4) include at least one selected from the group consisting of anions listed below.
[0084] Phosphite ion, dimethyl phosphite ion, ethylmethyl phosphite ion, diethyl phosphite ion, dibutyl phosphite ion, bis(2,4,4-trimethylpentyl)phosphite ion, dioctyl phosphite ion, ditetradecyl phosphinate ion, dioctyldecylphosphinate ion, dimethyl phosphate ion, diethyl phosphate ion and dibutyl phosphate ion. More preferably, at least one selected from the group consisting of diethyl phosphite ion and bis(2,4,4-trimethylpentyl)phosphite ion is selected, and more preferably, bis(2,4,4-trimethylpentyl)phosphite ion is selected.
[0085] However, from the viewpoint of further reducing the environmental dependence of the conductivity of the resin layer, the resin layer preferably contains the FSI anion as the only anion.
[0086] <Cation containing a double bond>
[0087] There is no particular limitation on the double-bond-containing cation as long as the cation has a double bond in the molecule. The cation is preferably not a cation of PFAS. That is, the cation preferably does not have a CF bond in the molecule.
[0088] The double bond-containing cation is preferably, for example, a cation having an aromatic heterocyclic structure, and particularly preferably a cation having a nitrogen-containing heterocyclic aromatic ring. Examples of the cation having a nitrogen-containing heterocyclic aromatic ring include a cation having an imidazolium structure and a cation having a pyridinium structure. That is, the double bond-containing cation is preferably at least one cation selected from the group consisting of a cation having an imidazolium structure and a cation having a pyridinium structure.
[0089] In particular, the double bond-containing cation is more preferably at least one cation selected from the group consisting of an imidazolium cation having an imidazolium structure represented by the following formula (2-1) and a pyridinium cation having a pyridinium structure represented by formula (2-2).
[0090]
[0091] In formula (2-1), R1 and R2 each independently represent a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms. From the viewpoint of effectively causing the interaction between the imidazolium cation and the aromatic ring-containing polyester, in the case where one selected from the group consisting of R1 and R2 is a hydrocarbon group having 5 to 8 carbon atoms (e.g., 8 carbon atoms), the other is preferably a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, more preferably a hydrocarbon group having 1 or 2 carbon atoms, and further preferably a hydrocarbon group having 1 carbon atom. More preferably, R1 and R2 each independently represent a hydrocarbon group having 1 to 4 carbon atoms.
[0092]
[0093] In formula (2-2), R3 and R4 each independently represent a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms. From the viewpoint of effectively causing the interaction between the pyridinium cation and the double bond-containing polyester, in the case where one selected from the group consisting of R3 and R4 is a hydrocarbon group having 5 to 8 carbon atoms (e.g., 8 carbon atoms), the other is preferably a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, more preferably a hydrocarbon group having 1 or 2 carbon atoms, and further preferably a hydrocarbon group having 1 carbon atom. More preferably, R3 and R4 each independently represent a hydrocarbon group having 1 to 4 carbon atoms.
[0094] Examples of the hydrocarbon group include linear and branched saturated hydrocarbon groups, linear and branched unsaturated hydrocarbon groups, substituted and unsubstituted saturated alicyclic hydrocarbon groups, substituted and unsubstituted unsaturated alicyclic hydrocarbon groups, and substituted and unsubstituted aromatic hydrocarbon groups. The hydrocarbon group is preferably an alkyl group.
[0095] Specific examples of the imidazolium cation represented by the above structural formula (2-1) include those listed below.
[0096] 1-ethyl-3-methylimidazolium cation, 1-butyl-3-methylimidazolium cation, 1-hexyl-3-methylimidazolium cation, 1-octyl-3-methylimidazolium cation and 1-octyl-3-methylimidazolium cation.
[0097] Specific examples of the pyridinium cation represented by the above structural formula (2-2) include those listed below.
[0098] 1-ethylpyridinium ion, 1-butylpyridinium ion, 1-hexylpyridinium ion, 1-octylpyridinium ion, 1-(tert-butyl)pyridinium ion, 1-octyl-4-methylpyridinium ion and 1-octyl-4-butylpyridinium ion.
[0099] Examples of the double bond-containing cation not having an aromatic heterocyclic structure include compounds in which a group having a vinyl group is bonded to at least one atom selected from the group consisting of carbon atoms and nitrogen atoms constituting a pyrrolidine ring or a piperidine ring.
[0100] One of the above cations can be used alone, or a combination of two or more thereof can be used. In addition, the resin layer, etc. can contain cations that do not have double bonds in the molecule as needed, as long as the advantageous effects of the present disclosure are not impaired. The ion conductive agent is composed of a combination of a fluorosulfonyl imide anion and one or more of these cations. For example, the resin layer, etc. contains an ion conductive agent including the above anions and cations.
[0101] In addition, the content of the ionic conductive agent in the resin layer (the total content of the fluorosulfonyl imide anion and the cation containing a double bond) is preferably 0.1% by mass or more relative to the mass of the resin layer. This is to make it easier to impart a prescribed level of conductivity to the resin layer. There is no particular restriction on the upper limit of this content, but it is, for example, 15.0% by mass or less. This is because if the content exceeds 15.0% by mass, even if the resin layer contains an ionic conductive agent, the conductivity improvement effect is limited.
[0102] The preferred range of the content of the ion conductive agent in the resin layer is 0.1 mass % to 15.0 mass %. The content should be appropriately selected within this range according to the conductivity to be exhibited by the resin layer. For example, the content of the ion conductive agent is more preferably 0.5 to 10.0 mass %, and further preferably 2.0 to 7.0 mass %.
[0103] In addition, it is possible to evaluate whether the ion conductor exists in the resin layer, etc. by extracting the ion conductor from the resin layer and identifying it. The solvent used for extraction should be selected from the solvent that can dissolve the ion conductor. Its specific example is methanol. If necessary, the extract can be centrifuged, or the ion conductor can be separated by liquid chromatography, and then the anion structure and the cationic structure can be identified using mass spectrometry or NMR analysis. In addition, by removing the solvent from the extract and then measuring the quality of the dry product, the total content of the anions and cations in the resin layer can be determined. The example of the method for identifying the cationic structure and the anion structure and its measurement quality will now be given.
[0104] 200 mg of sample was cut from the resin layer, immersed in 1 mL of methanol, and then irradiated with ultrasound at a frequency of 40 kHz for 10 minutes to obtain anion and cation extracts. Then a high-speed centrifugal separator was used to centrifuge at 12,000 rpm for 10 minutes, and the supernatant was collected to obtain a solution of cations and anions. Next, a liquid chromatography-mass spectrometer was used to perform mass spectrometry analysis on the obtained solution.
[0105] Mass spectrometry conditions
[0106] Direct introduction method
[0107] Injection volume: 2μL
[0108] Ionization method: electrospray ionization (ESI)
[0109] Furthermore, after removing the methanol solvent from the extract of cations and anions obtained using the above process, it was dissolved again in deuterated methanol to prepare a deuterated methanol solution of anions and cations, and 1 The deuterated methanol solution was measured by H-NMR.
[0110] Measurement conditions
[0111] Frequency: 400MHz
[0112] Accumulation times: 32
[0113] Measurement temperature: 25℃
[0114] The structures of cations and anions can be determined from mass spectrometry and 1 In addition, in the case where the solution does not contain a methanol-soluble component other than the ion conductive agent, the total amount of anions and cations contained in a 200 mg sample can be determined by measuring the mass of a dry product obtained by removing methanol from the solution.
[0115] <Additives>
[0116] The resin layer and the like may contain other components (additives) as long as the advantageous effects of the present disclosure are not impaired.
[0117] Examples of the additives include surfactants, antioxidants (e.g., hindered phenol-based antioxidants, phosphorus-based antioxidants, and sulfur-based antioxidants), ultraviolet radiation absorbers, organic pigments, inorganic pigments, pH adjusters, crosslinking agents, compatibilizers, release agents, coupling agents, lubricants, conductive fillers (e.g., carbon black, carbon fibers, carbon nanotubes, conductive tin oxide, and conductive mica), and polymer-type antistatic agents (e.g., polyether amides and polyether ester amides).
[0118] In addition, by adding hydrophilic metal oxide particles (silicon dioxide or titanium oxide, etc.), a conductive path is formed when ions migrate, which means that resistance can be significantly reduced. Therefore, the resin layer, etc. can contain hydrophilic metal oxide particles (silicon dioxide or titanium oxide, etc.). One of these additives can be used alone or in combination of two or more thereof. The amount of the additive can be appropriately specified and is not particularly limited. The content of the hydrophilic metal oxide particles is preferably 0.1 to 10.0 mass %, more preferably 0.5 to 3.0 mass % relative to the mass of the resin layer, etc.
[0119] The resin layer etc. may contain a polymer antistatic agent (eg, polyether amide or polyether ester amide). The content of the polymer antistatic agent is preferably 1.0 to 30.0% by mass, more preferably 5.0 to 20.0% by mass, based on the mass of the resin layer etc.
[0120] <Surface layer>
[0121] An example of the surface layer is a layer containing a cured product of an active energy ray-curable resin and exhibiting excellent wear resistance. This type of second layer can be provided by coating a composition containing an active energy ray-curable resin (such as a photocurable resin) on the peripheral surface of the base layer and then curing the composition. There is no particular limitation on the thickness of the surface layer, but, for example, it is preferably 1 to 5 μm.
[0122] <Back Layer>
[0123] Examples of the back layer include a resin layer for reinforcing the base layer and a conductive layer for imparting conductivity to the inner peripheral surface of the electrophotographic belt. The thickness of the back layer is not particularly limited, but is preferably 0.05 to 10 μm, for example.
[0124] In addition, a description will now be given using an electrophotographic belt as an example. There is no particular limitation on the application of the electrophotographic belt in an electrophotographic image forming apparatus, but an intermediate transfer belt for holding an unfixed toner image on an outer surface can be advantageously used, for example, as a transfer conveying belt for holding a recording medium on an outer surface. An electrophotographic member according to an embodiment of the present disclosure can be advantageously used for an intermediate transfer belt.
[0125] Furthermore, in the case where the electrophotographic member is used as an intermediate transfer belt, the surface resistivity ρs measured at the outer surface of the resin layer at a temperature of 23° C. and a relative humidity of 50% is preferably 1.0×10 6 to 9.9×10 12 Ω / □, more preferably 1.0×10 6 to 1.0×10 12 Ω / □, still more preferably 1.0×10 6 to 9.9×10 10 Ω / □.
[0126] If the surface resistivity is 1.0×10 6 Ω / □ or more, the transfer electric field can be more easily obtained during the secondary transfer, and the occurrence of spots and roughness in the electrophotographic image can be easily prevented. By making the surface resistivity 9.9×10 12Ω / □ or less, it is not necessary to excessively increase the transfer voltage during the secondary transfer, and the increase in the size of the power supply and the increase in cost can be better suppressed. In addition, depending on the conditions during the secondary transfer, transfer is possible even if the surface resistivity falls outside the above range, so the surface resistivity of the electrophotographic member is not necessarily limited to the above range.
[0127] <Production Method of Electrophotographic Member>
[0128] The resin layer can be formed using a conductive resin composition (eg, a resin composition obtained by melt-kneading these components) containing the above aromatic ring-containing polyester, fluorosulfonyl imide anions and double bond-containing cations (FSI ion conductive agent), and other additives as necessary.
[0129] For example, the following method can be used to form an electrophotographic member having the resin layer. That is, the electrophotographic member can be obtained by granulating the resin composition and then forming, for example, a seamless belt using a known molding method such as continuous melt extrusion molding, injection molding, stretch blow molding or inflation molding. The electrophotographic member is preferably an electrophotographic belt in the form of an endless belt. In addition, the electrophotographic member can be subjected to surface treatment, such as coating of a treatment agent or grinding treatment, as described above.
[0130] <Electrophotographic image forming apparatus>
[0131] use Figure 2 , a description will now be given of an electrophotographic image forming apparatus (electrophotographic apparatus) provided with an intermediate transfer member (hereinafter referred to as an intermediate transfer belt) as an electrophotographic member, but the present disclosure is not limited to this embodiment.
[0132] The electrophotographic image forming apparatus is preferably an apparatus in which the above-mentioned electrophotographic member is provided as an intermediate transfer belt. The intermediate transfer belt is a member for secondary transfer of the toner image transferred from the photosensitive drum to the recording material. In addition, Figure 2 is a schematic cross-sectional view showing one example of a full-color electrophotographic apparatus using an electrophotographic process.
[0133] This electrophotographic apparatus has a so-called tandem configuration in which electrophotographic stations of a plurality of colors are arranged in a row along the rotation direction of an electrophotographic member (intermediate transfer belt). In the description given below, symbols associated with yellow, magenta, cyan, and black are given suffixes Y, M, C, and k, respectively, but the suffixes may be omitted for similar configurations.
[0134] exist Figure 2In the image processing apparatus, charging devices 2Y, 2M, 2C and 2k, exposure devices 3Y, 3M, 3C and 3k, developing devices 4Y, 4M, 4C and 4k and an intermediate transfer belt 6 are arranged around photosensitive drums (photoreceptors, image bearing members) 1Y, 1M, 1C and 1k.
[0135] The photosensitive drum 1 is rotated and driven at a prescribed circumferential speed (process speed) in the direction indicated by the arrow F. The charging device 2 charges the circumferential surface of the photosensitive drum 1 to a prescribed polarity and potential (primary charging). As the exposure device 3, a laser beam scanner outputs an on / off modulated laser beam in response to image data input from an external device (not shown) such as an image scanner or a computer, and performs scanning exposure of the charged surface on the photosensitive drum 1. As a result of this scanning exposure, an electrostatic latent image corresponding to the target image data is formed on the surface of the photosensitive drum 1.
[0136] The developing devices 4Y, 4M, 4C, and 4k contain toners of different colors, namely yellow (Y), magenta (M), cyan (C), and black (k). In addition, the developing device 4 to be used is selected based on the image data, the developer (toner) is developed on the photosensitive drum 1, and the electrostatic latent image becomes visible as a toner image. In this embodiment, a reversal development method is used in which development is performed by making the toner adhere to the exposed portion of the electrostatic latent image. In addition, the electrophotographic means is composed of a charging device, an exposure device, and a developing device of this type.
[0137] The outer peripheral surface of the intermediate transfer belt 6 is arranged to contact the surface of the photosensitive drum 1, and the belt is stretched by a plurality of stretching rollers 20, 21, and 22. In addition, the belt rotates in the direction of arrow G. In the present embodiment, the stretching roller 20 is a tension roller for controlling the tension of the intermediate transfer belt 6 to a constant level, the stretching roller 22 is a roller for driving the intermediate transfer belt 6, and the stretching roller 21 is a counter roller for secondary transfer. In addition, primary transfer rollers 5Y, 5M, 5C, and 5k are provided at primary transfer positions facing the photosensitive drum 1 through the intermediate transfer belt 6.
[0138] By applying a primary transfer bias having a positive polarity (which is a polarity opposite to the charging polarity of the toner) to the primary transfer roller 5 by means of a constant voltage source or a constant current source, the colored unfixed toner image formed on the photosensitive drum 1 is electrostatically primary transferred sequentially on the intermediate transfer belt 6. In addition, by superimposing the unfixed toner images of four colors on the intermediate transfer belt 6, a full-color image is obtained. The intermediate transfer belt 6 rotates while holding the toner image transferred from the photosensitive drum 1. For each rotation of the photosensitive drum 1 after the primary transfer, the untransferred toner on the surface of the photosensitive drum 1 is repeatedly cleaned by the cleaning device 11 (11Y, 11M, 11C, and 11k), and the process then proceeds to the image forming step.
[0139] Furthermore, at a secondary transfer position on the intermediate transfer belt 6 facing the transfer path of the recording medium 7, a secondary transfer roller (transfer portion) 9 is pressed against the toner image holding surface of the intermediate transfer belt 6. Furthermore, a counter roller 21 which serves as a counter electrode of the secondary transfer roller 9 and applies a bias voltage is provided on the rear surface side of the intermediate transfer belt 6 at the secondary transfer position.
[0140] When the toner image on the intermediate transfer belt 6 is transferred to the recording medium 7, a bias voltage having the same polarity as the toner, such as -1000V to -3000V, is applied to the counter roller 21 by the secondary transfer bias applying means 28, and a current of -10μA to -50μA flows. At this time, the transfer voltage is detected by the transfer voltage detecting means 29. In addition, a cleaning device (belt cleaner) 12 for removing the toner remaining on the intermediate transfer belt 6 after the secondary transfer is provided on the downstream side of the secondary transfer position.
[0141] The recording medium 7 introduced from the registration roller pair 8 to the secondary transfer position is held and conveyed at the secondary transfer position, and at this time, a constant voltage bias (transfer bias) controlled to a specified value is applied from the secondary transfer bias applying means 28 to the counter roller 21 opposite to the secondary transfer roller 9. When the transfer bias having the same polarity as the toner is applied to the counter roller 21, the four-color full-color image (toner image) obtained by overlapping the transfer position on the intermediate transfer belt 6 is transferred to the recording medium 7 all at once, and a full-color unfixed toner image is formed on the recording material. After receiving the transferred toner image, the recording medium 7 is conveyed from the secondary transfer position in the direction indicated by the arrow H, introduced into the fixing unit (not shown), and thermally fixed.
[0142] Example
[0143] The present disclosure will now be described in more detail by using Examples and Comparative Examples, but the present disclosure is not limited thereto.
[0144] The measuring method and the evaluation method will now be explained by using Examples. Furthermore, in these Examples, a conductive belt as an intermediate transfer belt having an endless form was produced as an electrophotographic member.
[0145] (Measurement of surface resistivity)
[0146] The surface resistivity of the electrophotographic member was measured according to Japanese Industrial Standard (JIS) K6911:2006.
[0147] A high resistance meter (product name: Hiresta UP MCP-HT450, manufactured by Mitsubishi Chemical Analytech Co., Ltd.; main electrode inner diameter: 50 mm, guard ring electrode inner diameter: 53.2 mm, probe outer diameter: 57.2 mm (product name: UR-100, manufactured by Mitsubishi Chemical Analytech Co., Ltd.)) was used as a measuring device. A voltage of 250 V was applied to the electrophotographic member to be measured for 10 seconds, and the surface resistivity was measured at four positions in the circumferential direction of the outer surface of the resin layer of the electrophotographic member.
[0148] (ρs)
[0149] The electrophotographic member was placed in an environmental test room controlled to a temperature of 23° C. and a relative humidity of 50% for 12 hours. Next, using the above-mentioned measurement method, the surface resistivity was measured at four locations on the electrophotographic belt in an environment of a temperature of 23° C. and a relative humidity of 50%, and the arithmetic mean of the surface resistivity was taken as ρs (before power-on) and used as a resistance index.
[0150] The electrophotographic members obtained in Examples and Comparative Examples were mounted as intermediate transfer belts on a Figure 2 The intermediate transfer belt was placed on a transfer unit of a full-color electrophotographic apparatus (product name: HP Color Laser Jet CP4025dn, manufactured by Hewlett-Packard) having the configuration shown in FIG. Then, 200,000 sheets of cyan solid images were printed in a normal temperature and humidity environment (temperature of 25° C. and relative humidity of 55%). The intermediate transfer belt was then taken out from the electrophotographic apparatus, ρs was measured using the same method as described above, and the value was taken as ρs (after power-on).
[0151] The resistance change rate is defined as ((ρs(after power-on)-ρs(before power-on)) / ρs(before power-on)×100, and this is used as an indicator of resistance increase after continuous power-on.
[0152] (Image Evaluation)
[0153] When an image was formed using the above-mentioned electrophotographic apparatus, a 100th solid cyan image (hereinafter also referred to as "energization initial image") formed on an A4 size paper was visually observed, and the energization initial image quality was evaluated.
[0154] Furthermore, a final solid cyan image formed on an A4 size paper (hereinafter also referred to as a "final image") was visually observed, and the image quality after power-on was evaluated. The observation results were evaluated using the following criteria.
[0155] Rank A: No unevenness was observed at all.
[0156] Rank B: Some very slight unevenness was observed.
[0157] Rank C: Unevenness was observed in about 20% of the observed image.
[0158] Rank D: Unevenness is observed in at least half of the observed image.
[0159] Table 5 shows these evaluation results.
[0160] (Materials for Forming Resin Layer in Examples and Comparative Examples)
[0161] <Preparation of ion conductive agent>
[0162] [Ion conductive agents 1 to 3]
[0163] The following commercially available products were prepared as ion conductive agents 1 to 3.
[0164] Ion conductive agent 1:
[0165] 1-Ethyl-3-methylimidazoliumbis(fluorosulfonyl)imide (produced by Kanto Chemical Co., Inc.) Ion conductive agent 2:
[0166] 1-Butyl-3-methylimidazolium bis(fluorosulfonyl)imide (produced by Kanto Chemical Co., Inc.) Ion conductive agent 3:
[0167] 1-Octyl-4-methylpyridinium bis(fluorosulfonyl)imide (Product name: Elexcel AS-804, manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.)
[0168] Ion conductive agent 4: Ion conductive agent 4 was synthesized according to the following Production Example 1.
[0169] [Production Example 1: Synthesis of Ion Conductive Agent 4]
[0170] 50 mL of tetrahydrofuran (THF) (produced by Kanto Chemical Co., Inc.) was added to a round-bottomed flask equipped with a stirrer and a Dimroth condenser, 24.5 g of sodium hydroxide (produced by Kanto Chemical Co., Inc.) was dispersed in THF, and the round-bottomed flask was cooled using an ice bath. Next, a solution obtained by dissolving 17.0 g of imidazole (produced by Kanto Chemical Co., Inc.) as a nucleophile in 100 mL of THF was added dropwise to the round-bottomed flask. The ice bath was then removed and stirred for 2 hours at room temperature (23°C).
[0171] Next, 121.5 g of 1-bromooctane (produced by Tokyo Chemical Industry Co., Ltd.) was added to a round-bottomed flask as an electrophilic agent and heated under reflux for 8 hours at a temperature of 70° C. The reaction solution was filtered, the insoluble components were washed with THF, and the solvent in the resulting filtrate was distilled off under reduced pressure. The resulting concentrate was dissolved in dichloromethane again and filtered, the filtrate was recovered, and dichloromethane was distilled off under reduced pressure. The resulting concentrate was washed with diethyl ether and dried under reduced pressure to obtain a precursor of an ion conductive agent 4.
[0172] Next, the precursor of the entire amount of the ion conductor 4 was dissolved in 100 mL of methanol. While stirring the solution, 54.8 g of N, N-bis (fluorosulfonyl) imide potassium (product name: k-FSI, produced by Mitsubishi Materials Electronic Chemicals Co., Ltd.) dissolved in 100 mL of pure water was added, and stirred for 24 hours at room temperature. After the reaction, methanol was distilled off under reduced pressure, liquid separation was performed using dichloromethane / water, and the organic layer was recovered. The recovered organic layer was washed twice with pure water, the solvent was distilled off under reduced pressure, and the resulting product was dried to obtain an ion conductor 4 as a white powder.
[0173] Ion conductive agent 5: Ion conductive agent 5 was synthesized according to Production Example 2 below.
[0174] [Production Example 2: Synthesis of 5-Ion Conductive Agent]
[0175] 5.86 g of 12,13-tetracosanedione (produced by 1717CheMall Corp.), 0.58 g of paraformaldehyde (produced by Tokyo Chemical Industry Co., Ltd.) and 2.96 g of ammonium acetate (produced by Kanto Chemical Co., Inc.) were put into a round-bottom flask equipped with a stirrer and a Dimroth condenser, and these components were dissolved by adding 45.0 mL of ethanol (produced by Kanto Chemical Co., Inc.). Then, 1.0 mL of acetic acid (produced by Tokyo Chemical Industry Co., Ltd.) was added dropwise. Then, stirring was performed at a temperature of 110° C. for 4 hours.
[0176] Next, a saturated sodium bicarbonate aqueous solution was added so that the pH of the resulting reaction solution became 13. After pH adjustment, the reaction solution was subjected to liquid separation using dichloromethane / water, and the organic layer was recovered. The recovered organic layer was washed twice with pure water, the solvent was distilled off under reduced pressure, and the resulting product was dried to obtain a nucleophile (4,5-di-undecyl imidazole) as a white powder.
[0177] Hereinafter, an ion conductive agent 5 was obtained in the same manner as in Production Example 1 except that the nucleophilic agent used in Production Example 1 was changed to 4,5-di-undecylimidazole and the electrophilic agent used in Production Example 1 was changed to methyl iodide (produced by Tokyo Chemical Industry Co., Ltd.).
[0178] Materials used to form the resin layers in Examples and Comparative Examples are shown in the following Tables 1 to 2. Furthermore, specific materials used in Examples and Comparative Examples and their blending amounts are shown in the following Table 3. Furthermore, unless otherwise specified, the blending amounts are given as parts by mass.
[0179] Table 1 <Matrix resin>
[0180]
[0181] <Synthesis of Matrix Resin 3>
[0182] Polyethylene terephthalate resin (homobody, trade name: TRN-8550FF, manufactured by Teijin Ltd.) and polyethylene naphthalate (trade name: TN8065S, manufactured by Teijin Ltd.) were mixed in a molar ratio of 94:6, and the mixture was melt-kneaded at 300° C. to cause an ester exchange reaction between the two resins, thereby obtaining Matrix Resin 3.
[0183] Table 2 <Ion Conductive Agent>
[0184]
[0185] Table 3 <Other components>
[0186]
[0187] [Example 1]
[0188] The materials shown in Table 4 were melted and mixed in the blending amounts shown in Table 4 using a twin-screw kneading extruder (product name: PCM43, manufactured by Ikegai Corporation) to produce a resin composition.
[0189] Extrusion speed: 6kg / h
[0190] Screw speed: 225rpm
[0191] ·Cylinder temperature control: 270℃
[0192] The obtained resin composition was melt-extruded using a single screw extruder (manufactured by Research Laboratory of Plastics Technology Co., Ltd.) having a spiral cylindrical die (inner diameter: 195 mm, slit width: 1.1 mm) at its distal end under the conditions shown below to produce a cylindrical film having the dimensions shown below. The cylindrical film thus obtained was taken as the conductive tape of Example 1.
[0193] Extrusion speed: 6kg / h
[0194] Mold temperature: 290℃
[0195] ·Size: outer diameter 201mm, thickness 70μm
[0196] The evaluation results of the conductive tape are shown in Table 5 below.
[0197] [Examples 2 to 5 and 8 to 14]
[0198] Conductive tapes of Examples 2 to 5 and 8 to 14 were obtained in the same manner as in Example 1 except that the resin composition formulation was changed as shown in Table 4 below. The evaluation results of these tapes are shown in Table 5 below.
[0199] [Examples 6 and 7 and Comparative Example 2]
[0200] Conductive tapes shown in Examples 6 and 7 and Comparative Example 2 were obtained in the same manner as in Example 1 except that the resin composition formulation was changed as shown in Table 4 below, the barrel control temperature was changed to 240° C., and the mold temperature was changed to 260° C. The evaluation results of these tapes are shown in Table 5 below.
[0201] In Example 6 in which modified polyethylene terephthalate was used as the matrix resin, the conductive tape was not broken due to the decrease in crystallinity.
[0202] [Comparative Examples 1 and 3]
[0203] Conductive tapes shown in Comparative Examples 1 and 2 were obtained in the same manner as in Example 1 except that the resin composition formulation was changed as shown in Table 4 below, the barrel control temperature was changed to 200°C, and the mold temperature was changed to 220°C. The evaluation results of these tapes are shown in Table 5 below.
[0204] [Example 15]
[0205] The resin composition was prepared by hot melt kneading materials of the formulation shown in Table 4 below using a twin screw extruder (product name: TEX30α, produced by Japan Steel Works, Ltd.) The hot melt kneading temperature was adjusted to fall within the range of 260° C. to 280° C., and the hot melt kneading time was about 3 minutes.
[0206] The obtained resin composition was pelletized and then dried at a temperature of 140° C. for 6 hours.
[0207] Next, preforms were produced by supplying these pellets to an injection molding apparatus (product name: SE180EV-A, produced by Sumitomo Heavy Industries, Ltd.) having a reset cylinder temperature of 300° C. The injection molding mold temperature was 30° C.
[0208] The preform was softened by introducing it into a heating device at a temperature of 500° C. and heating it at 500° C. Next, the preform was placed in a primary blow molding device. Then, a blow-molded bottle was obtained by blow molding using a stretch rod and the force of air in a blow mold (blow air injection part) at a preforming temperature of 70° C., an air pressure of 0.3 MPa, and a stretch rod speed of 1000 mm / s.
[0209] Next, the obtained blow-molded bottle was placed in a secondary blow molding device, and a cylindrical nickel die was set to surround the outer circumference of the blow-molded bottle. Then, an air pressure of 0.1 MPa was applied inside the bottle, the blow-molded bottle was rotated around the inner surface of the die so that air did not leak to the outside, and the cylindrical die was uniformly heated at 200° C. for 60 seconds using a heater while rotating the cylindrical die. Next, the cylindrical die was cooled to a normal temperature of 23° C. using air, and the pressure applied to the inside of the bottle was released, thereby obtaining a heated blow-molded bottle.
[0210] Both ends of the heated blow-molded bottle were cut to obtain a single-layer conductive tape including only the resin layer. The obtained conductive tape had a thickness of 70 μm and a circumference of 792.0 mm. The evaluation results of the conductive tape are shown in Table 5 below.
[0211] Table 4
[0212]
[0213] In the table, CE stands for “Comparative Example.” Materials shown in Table 3 were used as other component 1 and other component 2.
[0214] Table 5
[0215] Example No. ρs(initial) ρs(after power on) Resistance change rate Initial image quality at power on Image quality after power on 1 6.3E+09 7.9E+09 26% A A 2 1.0E+10 1.3E+10 26% A A 3 2.5E+10 4.0E+10 58% A A 4 4.0E+10 1.3E+11 216% A A 5 3.2E+10 5.0E+10 58% A A 6 3.2E+10 5.0E+10 58% A A 7 5.0E+10 2.0E+11 298% A A 8 7.9E+10 1.0E+11 26% A A 9 1.0E+10 1.3E+10 26% A A 10 4.0E+10 5.0E+10 26% A A 11 2.0E+09 2.5E+09 26% A A 12 7.9E+10 1.0E+11 26% A A 13 1.6E+10 2.0E+10 26% A A 14 4.0E+10 5.0E+10 26% A A 15 6.3E+09 7.9E+09 26% A A CE1 1.0E+11 2.0E+12 1895% A C CE2 6.3E+10 3.2E+12 4912% A C CE3 6.3E+10 1.6E+12 2412% A C
[0216] In the table, for example, 6.3E+09 means 6.3×10 9 , CE stands for “Comparative Example”.
[0217] While the present invention has been described with reference to exemplary embodiments, it is to be understood that the invention is not limited to the disclosed exemplary embodiments.The scope of the following claims is to be accorded the broadest interpretation so as to encompass all such modifications and equivalent structures and functions.
Claims
1. An electrophotographic member, wherein The electrophotographic member comprises a resin layer, The resin layer has electrical conductivity, The resin layer comprises Polyesters containing aromatic rings and a fluorosulfonyl imide anion and a double bond-containing cation, and The aromatic ring-containing polyester is a polyester selected from the group consisting of the following polyesters (i) to (iv) or a mixture of two or more polyesters selected from the group consisting of the following polyesters (i) to (iv): (i) polyethylene naphthalate; (ii) polyethylene terephthalate; (iii) a modified polyethylene terephthalate in which the proportion of acid monomer units other than terephthalic acid units in all acid monomer units is 6 mol% or less; and (iv) A modified polyethylene naphthalate in which the proportion of the acid monomer units other than the naphthalene dicarboxylic acid units in all the acid monomer units is 6 mol% or less. 2 . The electrophotographic member according to claim 1 , wherein the double bond-containing cation has an aromatic heterocyclic structure.
3. The electrophotographic member according to claim 1 or 2, wherein the double bond-containing cation is at least one cation selected from the group consisting of a cation represented by the following formula (2-1) and a cation represented by the following formula (2-2): In the formula, R1, R2, R3 and R4 each independently represent a hydrogen atom or a hydrocarbon group having 1 to 8 carbon atoms.
4. The electrophotographic member according to claim 3, wherein In the case where one selected from the group consisting of R1 and R2 is a hydrocarbon group having 5 to 8 carbon atoms, the other is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms, and In the case where one selected from the group consisting of R3 and R4 is a hydrocarbon group having 5 to 8 carbon atoms, the other is a hydrogen atom or a hydrocarbon group having 1 to 4 carbon atoms. 5 . The electrophotographic member according to claim 3 , wherein R1, R2, R3 and R4 are each independently a hydrocarbon group having 1 to 4 carbon atoms.
6. The electrophotographic member according to claim 1 or 2, wherein The polyester containing aromatic rings is (i) polyethylene naphthalate; (ii) polyethylene terephthalate; or (iii) A modified polyethylene terephthalate in which the ratio of the acid monomer units other than the terephthalic acid units in all the acid monomer units is 6 mol% or less, and the acid monomer units other than the terephthalic acid units are isophthalic acid units.
7. The electrophotographic member according to claim 1 or 2, wherein The aromatic ring-containing polyester is polyethylene naphthalate or polyethylene terephthalate. 8 . The electrophotographic member according to claim 1 , wherein the sum of the content of the double bond-containing cation and the content of the fluorosulfonyl imide anion in the resin layer is 0.5 to 10.0% by mass relative to the mass of the resin layer.
9. The electrophotographic member according to claim 1 or 2, wherein the surface resistivity ρs measured on the outer surface of the resin layer at a temperature of 23° C. and a relative humidity of 50% is 1.0×10 6 to 1.0×10 12 Ω / □.
10. The electrophotographic member according to claim 1 or 2, wherein the electrophotographic member is an intermediate transfer member.
11. The electrophotographic member according to claim 1 or 2, wherein the electrophotographic member is an electrophotographic belt having an endless belt form.
12. An electrophotographic image forming apparatus, wherein The electrophotographic image forming apparatus comprises the electrophotographic member according to any one of claims 1 to 11 as an intermediate transfer member.
13. A conductive resin composition, wherein The conductive resin composition comprises Polyesters containing aromatic rings and a fluorosulfonyl imide anion and a double bond-containing cation, and The aromatic ring-containing polyester is a polyester selected from the group consisting of the following polyesters (i) to (iv) or a mixture of two or more polyesters selected from the group consisting of the following polyesters (i) to (iv): (i) polyethylene naphthalate; (ii) polyethylene terephthalate; (iii) a modified polyethylene terephthalate in which the proportion of acid monomer units other than terephthalic acid units in all acid monomer units is 6 mol% or less; and (iv) A modified polyethylene naphthalate in which the proportion of the acid monomer units other than the naphthalene dicarboxylic acid units in all the acid monomer units is 6 mol% or less.
Citation Information
Patent Citations
Conductive belt and electrophotographic device
JP2014132329A
Electrophotographic member, process cartridge, and electrophotographic image forming apparatus
JP2020024404A